Bentuk Kali Sekawan

Konsep Dasar

\(\displaystyle \lim_{x \rightarrow a} \dfrac {1}{\sqrt{x + m} - \sqrt{x + n}} \times \dfrac {\sqrt{x + m} + \sqrt{x + n}}{\sqrt{x + m} + \sqrt{x + n}} = \dfrac {\sqrt{x + m} + \sqrt{x + n}}{(x + m) - (x + n)}\)

 

Penjelasan

\((a + b)(a - b) = a^2 - b^2\)

\((\sqrt{a} + \sqrt{b})(\sqrt{a} - \sqrt{b}) = (\sqrt{a})^2 - (\sqrt{b})^2 = a - b\)

\((\sqrt{x + m} + \sqrt{x + n})(\sqrt{x + m} - \sqrt{x + n}) = (\sqrt{x + m})^2 - (\sqrt{x + n})^2 = (x + m) - (x + n)\)

(Next Lesson) Contoh Soal 01
Kembali ke Bentuk Kali Sekawan